Long-run waves or short-run fluctuations – what establishes the correlation between oil and food prices?. Issue 54 (20th November 2017) - Krätschell, Karoline; Schmidt, Torsten
ABSTRACT: The strong correlation between food prices and energy prices has gained much attention in the public debate. In this article, we focus on the so-called excess co-movement, which is the correlation between crude oil price and the prices of food commodities after controlling for economic activity. We use a frequency domain Granger causality test to analyse short-run and long-run relationships between crude oil prices and prices of food commodities. For important biofuel inputs like maize, soybeans, rapeseed and EU sugar, we find evidence for long-run Granger causality in particular for the period after 2007. This supports the hypothesis that the increasing biofuel production creates the link between the prices of crude oil and food commodities. However, we also find short-run Granger causality for various food commodities. This result is more in line with herd behaviour or speculation in commodity markets.